Mortality due to HIV-AIDS in the state of Piauí between 2008 to 2018 (Research, Society and Development, 2021)
The present study aimed to determine mortality from HIV / AIDS in the State of Piauí and its relationship with socioeconomic indicators (Human Development Index and Gini Index) from 2008 to 2018, describing gender, age group, year and place of death and the basic cause of death according to the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision (ICD-10). In a quantitative approach to obtaining data on mortality, the research used secondary data provided by the State Department of Health of the State of Piauí (SESAPI) and to obtain data on the HDI and Gini Index, platforms were used from the Brazilian Institute of Geography and Statistics (IBGE) and DATASUS / TABNET, respectively. According to the data obtained, 1280 deaths were recorded in the period studied, where 70.36% occur in males, aged 30 to 39 years (33%) and mainly due to HIV resulting in infectious and parasitic diseases (64%). The prevalence of deaths occurred in the state capital, Teresina, especially in the first years analyzed. With regard to the HDIm and the average Gini index by development territory, there is a relationship with the deaths that occurred in the State. There was an increase in the mortality rate in the period studied, observing a slight drop in 2010, confirming a public health problem in the State of Piauí.